Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Guru Terhadap Prestasi Peserta Didik di Kecamatan Kuta Cot Glie Kabupaten Aceh Besar - Afriani, Nur; Rahmattullah, Rahmattullah; Musdiani, Musdiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to determine the influence of academic supervision and managerial leadership of school principals on the work motivation of elementary school teachers in Kuta Cot Glie District, Aceh Besar Regency. This research uses survey research methods. Hypothesis testing uses simple linear regression analysis, multiple linear regression analysis, multiple correlation analysis (R), determination analysis (R2), and combined regression coefficient test (F test). The results of the research are that there is a significant influence between academic supervision on teacher work motivation in Kuta Cot Glie District, Aceh Besar Regency; there is a significant influence between the managerial leadership of school principals on teacher work motivation in Kuta Cot Glie District, Aceh Besar Regency; there is a significant influence between the principal's academic supervision and managerial leadership on teacher work motivation at the State Elementary School, Indrapuri District, Aceh Besar Regency; The contribution of academic supervision to teacher work motivation was 38.8%; the contribution of the principal's managerial influence to teacher work motivation was 51.3%; The contribution of the influence of Principal Leadership and School Teacher Work Motivation on Student Learning Achievement is 57.8%